Perencanaan Kebutuhan Bahan Baku untuk Memenuhi Permintaan pada Produksi Wheeldop - Karisma Dwi Rahayu; Siti Mundari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD XYZ is a company engaged in the metal industry, with its main product being wheeldops (wheel covers). The main problem faced by the company is the lack of raw material inventory planning for steel plates, resulting in stockouts that disrupt the production process and delay order fulfillment. This study aims to determine the optimal order quantity, appropriate reorder timing, and the required level of safety stock to minimize the risk of stockouts and inventory costs. The methods used in this study are the Continuous Review System (CRS) and the Periodic Review System (PRS). Based on the comparison results, CRS has a lower total inventory cost of Rp 1,712,173,383 compared to PRS. The model was then developed into a Continuous Review System with Backorder by considering a backorder cost of Rp 295,000 per sheet, resulting in an order quantity of 424 sheets, a safety stock of 83 sheets, and a reorder point of 120 sheets. This policy is intended to anticipate the risk of stockouts caused by raw material delivery delays during the lead time.